2019
DOI: 10.1515/dx-2018-0066
|View full text |Cite
|
Sign up to set email alerts
|

Internal medicine residents’ evaluation of fevers overnight

Abstract: Background Scant data exists to guide the work-up for fever in hospitalized patients, and little is known about what diagnostic tests medicine residents order for such patients. We sought to analyze how cross-covering medicine residents address fever and how sign-out systems affect their response. Methods We conducted a prospective cohort study to evaluate febrile episodes that residents responded to overnight. Primary outcomes included diagnostic tests ordered, if an in-person evaluation occurred, and the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…[ 12 ] This practice of reflexive blood culture ordering was found to be more prevalent among cross-covering residents at night shift. [ 23 , 24 ] Potential explanation for this observation in the survey include fewer staffing and supervision, and less familiarity with the patients during night shifts and on the weekends. [ 25 ] Our study expands on previous studies [ 12 , 13 ] by providing a better understanding on how variation in shift work and day of the week may influence the clinical decision making around blood culture.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] This practice of reflexive blood culture ordering was found to be more prevalent among cross-covering residents at night shift. [ 23 , 24 ] Potential explanation for this observation in the survey include fewer staffing and supervision, and less familiarity with the patients during night shifts and on the weekends. [ 25 ] Our study expands on previous studies [ 12 , 13 ] by providing a better understanding on how variation in shift work and day of the week may influence the clinical decision making around blood culture.…”
Section: Discussionmentioning
confidence: 99%
“…There is no standardized approach, and little is known about how physicians respond to fever and the diagnostic tests that are commonly used. 1 In a systematic review by Kaul et al, the incidence of hospital-acquired fever ranged from 2% to 17%, with infections accounting for 37–74% of the cases. 2 Invasive procedures are considered a risk factor for hospital-acquired infections, and the most common infections are pneumonia, urinary tract infections, and bloodstream infections.…”
Section: Introductionmentioning
confidence: 99%
“…3 Therefore, these infections are the likely cause of hospital-acquired fever. However, the effects of early intervention in such cases have not been studied, 1 and the actual response likely depends on the clinical situation. For example, some studies have shown no significant difference in the timing of antimicrobial administration within 24 h in patients with febrile neutropenia; 4 however, for bacteremia caused by Staphylococcus aureus , even a delay of 1 day in the treatment increases the risk of death.…”
Section: Introductionmentioning
confidence: 99%